"Mon cher ami": Friendship in Le Bourgeois gentilhomme. Issue 2 (July 2017) - Weeden, Kirk
Abstract : Molière's ideological position in regard to the nobility and bourgeoisie of his era is a hotly contested subject. This article contributes to this ongoing debate by offering a reading of friendship in Le Bourgeois gentilhomme. In particular, it analyses the relationship between the bourgeois protagonist, Monsieur Jourdain, and the count Dorante. It seeks to understand this relationship in terms of friendship by referring to the influential philosophical construction of friendship proposed by Cicero in Laelius de amicitia . It argues that both characters fall short of the conditions required for such a friendship, leaving them equally open to criticism. While there appears to be weightier judgment reserved for Dorante's conduct, this is problematized by considering the cultural phenomenon of honnêteté in seventeenth-century France, which complicates the Ciceronian conception of friendship. The analysis suggests the need for a wider reading of Molière's works to further explore this socio-cultural tension.